América latina transterritorial: percursos em fronteiras fluidas - Costa, Maria Luiza Calim de Carvalho [UNESP] (My University, 2013)
Contemporary artists have proposed repositioning of the view as a psicogeographics, routes of drifts, affectives maps, subverting the physical, historical, political and social places in the global mapping. The Chilean artist Eugenio Dittborn with their "Airmail Paintings" that design, sewing, painting and collage are folded and placed in an envelope and sent by post. At your destination, the paint is removed from the envelope, unfolded and hung leaving the marks of the route traveled. The Argentine artist Alicia Herrero in his work "The trip Revoluvionário - title inspired by the trip that Ernesto Guevara held in South America, traveled by navigable rivers of South America and composed the work in the form of a" novel navigated "where each chapter is a port route. As the river of Heraclitus, the writing of "novel navigated" composes processes transposing borders.
Keywords: Latin America; Contemporary art; Alicia Herrero; Eugenio Dittborn; 8a. Bienal do Mercosul